P1194RISK FACTORS FOR CARDIOVASCULAR DEATH IN NON-DIABETIC PERITONEAL DIALYSIS PATIENTS. (6th June 2020) - Andronesi, Andreea Gabriella; Iliuta, Luminita; Cristache, Cristina; Sorohan, Bogdan Marian; Lupusoru, Gabriela Elena; Andronesi, Danut; Lupusoru, Mircea; Obrisca, Bogdan; Ismail, Gener
Abstract: Background and Aims: Chronic kidney disease and especially end stage renal disease are important public health issues with increasing incidence and significant economic burden. Despite advances in peritoneal dialysis (PD), mortality is still high mostly because of cardiovascular morbidity and mortality. The aim of the present study was to identify prognostic risk factors for cardiovascular death in non-diabetic PD patients. Method: We performed a prospective study in which we included non-diabetic patients in stable PD programme for at least 6 months. Clinical, biological, heart and carotid ultrasound and arterial stiffness (evaluated through applanation tonometry) parameters were analysed. Independent risk factors for cardiovascular death were identified by logistic regression using IBM SPSS ver. 20.0. Results: We included 246 consecutive non-diabetic patients (118F, 128M), mean age 56.3 + 15.7 years (20-85). Mean follow up was 6.5+ 1.1 years. 36 patients (14.6%) died because of cardiovascular reasons - sudden cardiac death 13 patients, acute coronary syndrome 8 patients, ischemic stroke 8 patients, and heart failure 7 patients. Individuals with cardiovascular death were significantly older (64.6±14.2 vs 54.7±15.5 years, p=0.01), with signs of malnutrition, inflammation and associated anemia - significantly lower total cholesterol (150.2±43.0 vs 194.3±58.2 mg/dl, p=0.002), serum albumin (2.9±0.4 vs 3.5±0.7 g/dl, p=0.002) and hemoglobin (9.7±1.1 vs 10.7±1.4 g/dl, p=0.007) and significantly higher serum fibrinogen (568.7±121.3 vs 509.8±115.0 mg/dl, p=0.04) and C-reactive protein (6.7+ 1.2 vs 9.5+ 0.9 mg/l, p=0.02). In univariate analysis risk for cardiovascular death was higher in patients with renal hypertensive disease (OR 4.0, 95%CI 1.4-11.5, p=0.01), iPTH serum level <150 pg/ml (OR 6.6, 95%CI: 2.3-18.9, p<0.001), left ventricular hypertrophy (OR 10.6, 95%CI 2.3-18.9, p=0.001) and diastolic dysfunction (OR 4.0, 95%CI 1.2-14.9, p=0.02). Compared to patients with an iPTH between 150-300 pg/ml, both patients with lower iPTH and also higher iPTH had an increased risk for cardiovascular death (OR=1.6, 95%CI: 1.2-2.0; p<0.001 for iPTH<150 pg/ml, and OR =1.2, 95%CI:1.04-1.34; p=0.01 for iPTH<300 pg/ml). Patients with cardiovascular death had signs of subclinic atherosclerosis- intima-media thickness at carotid level >0.9 mm (OR 4.3, 95%CI 1.1-16.3, p=0.02) and higher pulse wave velocity as a sign of increased arterial stiffness (11.9+ 2.5 vs 8.6+ 2.6 m/s, p=0.04). After adjusting for potential confounders, independent predictive factors for cardiovascular death were male gender, calcium-phosphate product>55 mg 2 /dl 2, iPTH<150 pg/ml and peripheral arterial disease (Table 1). Conclusion: We found an increased risk for cardiovascular death in non-diabetic PD patients, mostly because of sudden cardiac death. Malnutrition, inflammation, but especially abnormal mineral metabolism (both increased calcium-phosphate product and low bone turnover) were identified as risk factors for cardiovascular death and are potentially treatable risk factors to improve cardiovascular outcome in PD patients. A better understanding of pathogenesis and risk factors for cardiovascular death in PD may help improve patients' management and thus their long-term survival.